Challenges to the Radio of the Republic of Indonesia as a Public Broadcasting Institution to Enter Political Contestation in the 2024 Elections (Open Society Conference, 2023)
As a public broadcasting institution, Radio Republik Indonesia (RRI) has a big role for the progress of the nation, especially in providing information services to the public. At the current stage of the 2024 election, there is a big challenge in being able to demonstrate the nature and duties as stipulated in Government Regulation Number 12 of 2005. This research aims to examine the various challenges facing itself as a public broadcasting institution which must be fully oriented to the public interest. This study uses a combination of normative juridical methods, literature review and document study. In elections as a political process, their nature which must be independent will be faced with their determination not to be influenced by other parties. Its nature to be neutral will be demonstrated by its consistency in not taking sides with the interests of political actors who have different opinions. The challenge of being non-commercial will be faced with its commitment to prioritize services to the community without abandoning its commerciality. Organizationally, he is under and responsible to the President of the Republic of Indonesia, facing a big challenge to be consistent with his duties, especially as a means of social control. Other major challenges relate to the quality of information services, the intensity of educational tasks, healthy entertainment, social bonding in a pluralistic society and the task of preserving national culture.